THE PRAGMATIC ANALYSIS OF EXCLAMATORY AND EXPRESSIVE UTTERANCES IN LION KING MOVIE (1994) - Aplonia Nelci Ke Lomi Lomi; Yunika Upa (ELTR Journal, 2018)
Communication is very important to our life. It is a kind of media that used to express our intentions, ideas, feelings or information to the listeners or audiences. One of important aspects in the communication is speech acts. Speech acts consist of many categories; one of them is exclamatory and expressive utterances. This study aims to identify exclamatory and expressive utterances performed in the Lion King movie (1994). Likewise, it will find out the type of exclamatory and expressive utterances that are most frequently used in the movie and the other expressive utterances that are found. This study used the qualitative method, reading the transcript, watching the movie and library research. The study also revealed the importance of learning types of utterances in and unique utterances that. This study is expected to give some useful insights into understanding what exclamatory and expressive utterances are.